Experimental investigation of wave-in-deck impact events on a TLP model. (15th September 2017) - Abdussamie, Nagi; Drobyshevski, Yuriy; Ojeda, Roberto; Thomas, Giles; Amin, Walid
Abstract: Model tests were conducted to investigate the global response of a conventional tension leg platform (TLP) due to wave-in-deck loads associated with extreme wave events in irregular long-crested waves of a cyclonic sea state. The experimental setup was designed to allow for the simultaneous measurement of wave surface elevations, rigid body motions, tendon tensions, as well as the pressure distribution at the model's deck underside. The obtained results demonstrated the variability of all the measurements and provided insights into the effect of wave-in-deck loads on the platform behaviour, tendon tensions and slamming pressures and showed qualitative correlations between these parameters. Based on the repeated tests in several events with different wave parameters, general observations and conclusions were made with respect to the platform dynamics during the deck impact, tendon tensions, slack tendon situations, tendon ringing and local impact pressures. The results of this study could be used for calibrating computational fluid dynamics (CFD) tools. Highlights: Reliable experimental data of wave-in-deck loads on a TLP model due to extreme wave conditions are provided for CFD validations. The wave-in-deck impact events cause ringing response in the up-wave and down-wave tendons. Following a wave-in-deck impact event, the down-wave tendons experience slackness.